Is it a food web or a food chain? - Sohn, Emily (Science inquiry., 2022)
"A seed falls from a plant. A mouse eats the seed. An owl eats the mouse. Each animal gets energy from its food. How does energy flow from one living thing to another? Let's investigate food chains and food webs!"--Provided by publisher.